INSURANCE RISKS IN THE ACTIVITY OF BUSINESS SUBJECTS AND ISSUES OF THEIR REDUCTION - Sh. J. Mamadjanov (Web of Journals Publishing, 2023)
The article presents risks in small business and private entrepreneurship activities, their types, assessment criteria and reduction issues.
Keywords: entrepreneurship, natural risks, insurance tariffs, insurance event, insurance coverage, tariff rate.